THE EFFECT OF THE FILLET THICKNESS ON THE SMOKED TUNA (Euthynnus sp.) FILLET QUALITY AND STABILITY DURING STORAGE IN COLD TEMPERATURE (5 ± 2 0C) - Ansyor Refinal Fadilah Nasution; Tjipto Leksono; Bustari Hasan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT This study aimed to determine the effect of thickness on the quality and stability of smoked tuna (Euthynnus sp) fillet during storage in cold temperature (5 ± 2 oC). The treatment conducted was immersing tuna fillet in a liquid smoke solution at a concentration of 4% for 60 minutes at varied thickness (1, 1.5, and 2 cm) and then stored them in a refrigerator for 0, 2, 4, and 6 days. The results showed that the thickness of tuna fillet had an effect on the organoleptic value (appearance and odor), chemical value (pH and TMA) and also the total bacteria number (TPC). The best quality of the liquid smoked tuna fillet was shown by the thickness of 1.5 cm. After stored for 4 days, the best quality tuna fillet was also showing the highest value of appearance at 6.5, with the characteristics of white meat and red meat is less bright, clean, neat, not damaged; the value of odor 6.6, characterized by the specific smoky aroma; and the value of texture 6.4 with characteristics quite elastic, slightly soft and compact. The chemical characteristics was showing the value of pH 6.1, Trimethylamine 2.97 mgN / 100g, water activity 0.74, and the total number of bacteria 9,4x103 cfu/g, after stored for 6 day.Keywords: fillet, thickness, cold temperature (5 ± 2 0C)